Women Leadership in Indian Organizations (Global Journal of Management and Business Research, 2020)
In today#x2019;s global economy, industries require a talented pool of candidates to create a comparative competitive advantage to address the global opportunities as well as to address these global trends and dynamic challenges factual and cognitive leadership is required to manage changes effectively. The nurturing and task-oriented style, managerial practices, organizational orientation, especially followed by women entrepreneurs/ leaders/ managers has carved a niche for women leadership in national as well as international platforms. The current financial crisis and long-term global trends are reshaping the corporate landscape, and there is an urgent need to accelerate some of the changes in corporations to seize the new opportunities that arise from time to time.
Keywords: women leaders; glass-ceiling; leadership programs; gender diversity; stereotyping; perceptions; barriers; styles